1994
DOI: 10.1016/s0969-2126(00)00068-x
|View full text |Cite
|
Sign up to set email alerts
|

The molecular structure of the complex of Ascaris chymotrypsin/elastase inhibitor with porcine elastase

Abstract: The structure of the C/E-1 inhibitor confirms that inhibitors from Ascaris suum belong to a novel family of proteinase inhibitors. It also provides conclusive evidence for the correct disulfide bridge connections. The C/E-1 inhibitor probably acts by a common inhibitory mechanism proposed for other substrate-like protein inhibitors of serine proteinases. The unusual molecular scaffolding presents a challenge to current folding algorithms. Proteins like the C/E-1 inhibitor may provide a valuable model system to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 60 publications
(77 reference statements)
3
62
0
Order By: Relevance
“…Here we present our analysis of one of the two main components of this fraction. As we have shown, this is a trypsin inhibitor related to the protease inhibitors from Ascaris (Grasberger et al, 1994;Huang et al, 1994).…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Here we present our analysis of one of the two main components of this fraction. As we have shown, this is a trypsin inhibitor related to the protease inhibitors from Ascaris (Grasberger et al, 1994;Huang et al, 1994).…”
mentioning
confidence: 76%
“…The scissile peptide bond in these inhibitors is between residues 31 and 32. These are in the sequence Cys-ProLeu/Met-Cys in the chymotrypsin/elastase and Cys-Thr-Arg/ Glu-Cys in the trypsin inhibitor (Peanasky et al, 1984;Grasberger et al, 1994;Huang et al, 1994). At the homologous positions of the BSTI peptide, the sequence Cys-Asp-Lys-Lys-Cys is present, which in fact suggested that this acts as an inhibitor of trypsin-like enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…comm.). Such a discrepancy was recently reported for the Ascaris chymotrypsin/elastase inhibitor, for which disulfide bridges found both by NMR and X-ray agree but disagree with biochemical studies (Grasberger et al, 1994;Huang et al. 1994).…”
Section: Discussionmentioning
confidence: 58%
“…By using RT-PCR, we successfully amplified a cDNA whose translated amino acid sequence showed limited homology to the anticoagulants from A. caninum, AcAP5 and AcAPc2. The 40 -44% amino acid sequence identity (52-55% similarity) to the two AcAP sequences, in addition to the conservation and alignment of the 10 cysteine residues, which are known to play a critical role in defining the tertiary molecular structure of the Ascaris type inhibitors (9,33,34), suggests that AceAP1 is, in fact, a member of this family of nematode proteins. In addition to those from Ancylostoma hookworms, Ascaris-type inhibitors have also been identified other nematode species, including A. suum (7,8), Anisakis simplex (35), and Trichuris muris (36).…”
Section: Discussionmentioning
confidence: 99%